2015
DOI: 10.1002/ajmg.a.37448
|View full text |Cite
|
Sign up to set email alerts
|

Craniosynostosis in 10q26 deletion patients: A consequence of brain underdevelopment or altered suture biology?

Abstract: Approximately a hundred patients with terminal 10q deletions have been described. They present with a wide range of clinical features always accompanied by delayed development, intellectual disability and craniofacial dysmorphisms. Here, we report a girl and a boy with craniosynostosis, developmental delay and other congenital anomalies. Karyotyping and molecular analysis including Multiplex Ligation dependent probe amplification (MLPA) and Array Comparative Genomic Hybridization (aCGH) were performed in both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…A de novo variant (c.487C>T, p.(Arg163Trp)) was identified in EBF3 , which was considered a gene of uncertain significance at the time of analysis (Table 1). This variant was reported due to EBF3 being implicated as part of the critical region in the 10q26 microdeletion syndrome, which has features overlapping the clinical phenotype of the proband (Faria et al 2016). In silico analyses predicted that this alteration was deleterious, probably damaging, and disease-causing by SIFT (Sorting Intolerant from Tolerant), PolyPhen-2, and MutationTaster2, respectively (Kumar et al 2009; Adzhubei et al 2010; Schwarz et al 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A de novo variant (c.487C>T, p.(Arg163Trp)) was identified in EBF3 , which was considered a gene of uncertain significance at the time of analysis (Table 1). This variant was reported due to EBF3 being implicated as part of the critical region in the 10q26 microdeletion syndrome, which has features overlapping the clinical phenotype of the proband (Faria et al 2016). In silico analyses predicted that this alteration was deleterious, probably damaging, and disease-causing by SIFT (Sorting Intolerant from Tolerant), PolyPhen-2, and MutationTaster2, respectively (Kumar et al 2009; Adzhubei et al 2010; Schwarz et al 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Prior to recent reports, EBF3 had not been implicated definitively in any disorder in humans. However, patients with 10q26 microdeletion syndrome that includes a 3.5 Mb minimally deleted region (SROII) involving EBF3 have several overlapping clinical features with individuals carrying EBF3 intragenic variants, including short stature, craniofacial dysmorphisms, strabismus, abnormal ears, genital anomalies, urinary tract anomalies, CNS malformations, microcephaly, and intellectual disability (Faria et al 2016). As in ARX-related disorders, variants in EBF3 are associated with marked phenotypic and clinical heterogeneity, with some patients presenting with structural brain abnormalities and others having no evidence of CNS malformations.…”
Section: Discussionmentioning
confidence: 99%
“…Majority of the children in the age group of 1 to 5 years that were diagnosed to have 10q deletions, were originally referred to genetics teams, because of undiagnosed dysmorphic features, and severe developmental delays 3,6,13,17,18 . Unlike adults, there was no strong gender predisposition among pediatric cases 2,8,9,11 . There was a significant representation of teens among those that were diagnosed with 10q deletions 2,6,8,17 .…”
Section: Age At Diagnosis and Gendermentioning
confidence: 95%
“…The severity and clinical characteristics of patients with a deletion in this region vary widely, not only due to the length of deletion, but also based on location of the deletion. Faria et al 9 , and Yatsenko et al 13 , postulated that DOCK1 is the smallest region of overlap (SRO I) that was responsible for clinical signs (phenotype). Faria et al also suggested a second 3.5 Mb region (SRO II) was also important for the presentation of the phenotype.…”
Section: Genetic and Clinical Implications Of 10q Deletionsmentioning
confidence: 99%
“…Discrete smallest regions of overlap (SRO) delineating the critical regions that may contain the gene(s) or genetic elements responsible for the major craniofacial, cardiac, and neuropsychiatric clinical features of patients with 10q monosomy have been proposed previously (Faria et al, ; Yatsenko et al, ). Similarly, critical regions for sex determination, hearing and vestibular function, urogenital defects, speech delay, and craniosynostosis have also been described (Faria et al, ; Miller et al, ; Yatsenko et al, ). With the addition of new patients to those previously described in the literature, these regions can be further refined and additional regions can be identified to provide new insight into the genes contributing to specific clinical features when present in a haploinsufficient state.…”
Section: Introductionmentioning
confidence: 99%